2021
DOI: 10.1002/cbic.202100301
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐PAINT Enables Investigation of Endogenous Talin with Molecular Scale Resolution in Cells and Tissues

Abstract: Talin is a cell adhesion molecule that is indispensable for the development and function of multicellular organisms. Despite its central role for many cell biological processes, suitable methods to investigate the nanoscale organization of talin in its native environment are missing. Here, we overcome this limitation by combining single-molecule resolved PAINT (points accumulation in nanoscale topography) imaging with the IRIS (image reconstruction by integrating exchangeable singlemolecule localization) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Significant advances in cell imaging at the sub-nanometre level for single molecule analysis using Quantum imaging techniques [ 153 ] have provided important advances in the assessment of cellular changes in disease processes and the roles of specific proteins [ 154 , 155 ]. Peptide painting of single molecules with quantum dot semi-conductor nanoprobes [ 156 , 157 ] has enabled the examination of specific contributions single molecules make to cellular phenotypes [ 155 , 158 , 159 ]. Quantum dots are fluorescent nanoparticles with narrow-band, size-tuneable, and long-lasting emission profiles [ 160 ], which have proved useful in molecular imaging in cancer medicine [ 161 ].…”
Section: Analysis Of Glycan Structure and Functionmentioning
confidence: 99%
“…Significant advances in cell imaging at the sub-nanometre level for single molecule analysis using Quantum imaging techniques [ 153 ] have provided important advances in the assessment of cellular changes in disease processes and the roles of specific proteins [ 154 , 155 ]. Peptide painting of single molecules with quantum dot semi-conductor nanoprobes [ 156 , 157 ] has enabled the examination of specific contributions single molecules make to cellular phenotypes [ 155 , 158 , 159 ]. Quantum dots are fluorescent nanoparticles with narrow-band, size-tuneable, and long-lasting emission profiles [ 160 ], which have proved useful in molecular imaging in cancer medicine [ 161 ].…”
Section: Analysis Of Glycan Structure and Functionmentioning
confidence: 99%
“…[12][13][14] While DNA oligos are commonly used in PAINT, peptides that hybridize to each other have recently been used (named Peptide-PAINT). 10,[15][16][17][18][19] For example, Fischer et al used a fluorescently labeled imager peptide in fixed cells to transiently bind to the extracellular side of talin, a protein involved in cell adhesion process. 16 This particular system is highly advantageous as the protein-of-interest (talin) already has a binding site for the imager, and hence there is no need to have an external docker-peptide.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] We, here, mention that qPAINT requires a calibration curve to get the binding rate at different imager concentrations, and this method is not yet established or possible for Peptide-PAINT.While DNA oligos are commonly used in PAINT, peptides that hybridize to each other have recently been used (named Peptide-PAINT). [10,[17][18][19][20][21] For example, Fischer et al used a fluorescently labeled imager peptide in fixed cells to transiently bind to the extracellular side of talin, a protein involved in cell adhesion process. [18] This particular system is highly advantageous as the protein-of-interest (talin) already has a binding site for the imager; and hence, there is no need to have an external docker-peptide.Another example of Peptide-PAINT is SYNZIP17-SYNZIP18, a coiled-coil peptide pair that was employed for imaging intracellular targets in live yeast cells where both the docker, genetically appended to the target-of-interest, and the imager, conjugated to Point accumulation for imaging in nanoscale topography (PAINT) is a single-molecule technique for super-resolution microscopy, which uses exchangeable single stranded DNA oligos or peptide-pairs to create blinking phenomenon and achieves ≈5-25 nanometer resolution.…”
mentioning
confidence: 99%
“…[10,[17][18][19][20][21] For example, Fischer et al used a fluorescently labeled imager peptide in fixed cells to transiently bind to the extracellular side of talin, a protein involved in cell adhesion process. [18] This particular system is highly advantageous as the protein-of-interest (talin) already has a binding site for the imager; and hence, there is no need to have an external docker-peptide.Another example of Peptide-PAINT is SYNZIP17-SYNZIP18, a coiled-coil peptide pair that was employed for imaging intracellular targets in live yeast cells where both the docker, genetically appended to the target-of-interest, and the imager, conjugated to Point accumulation for imaging in nanoscale topography (PAINT) is a single-molecule technique for super-resolution microscopy, which uses exchangeable single stranded DNA oligos or peptide-pairs to create blinking phenomenon and achieves ≈5-25 nanometer resolution. Here, it is shown that by transfecting the protein-of-interest with a docker-coil, rather than by adding the docker externally-as is the norm when using DNA tethers or antibodies as dockers-similar localization can be achieved, ≈10 nm.…”
mentioning
confidence: 99%
See 1 more Smart Citation